2018
DOI: 10.1038/s41598-018-29645-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional alterations during proliferation and lignification in Phyllostachys nigra cells

Abstract: Highly-lignified culms of bamboo show distinctive anatomical and mechanical properties compared with the culms of other grass species. A cell culture system for Phyllostachys nigra has enabled investigating the alterations in cellular states associated with secondary cell wall formation during its proliferation and lignification in woody bamboos. To reveal transcriptional changes related to lignification in bamboo, we analyzed transcriptome in P. nigra cells treated with the synthetic auxin 2,4-dichlorophenoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In glossaries, for example [ 7 ], stem cell developmental potency is classified into several types: unipotent, a stem cell able to develop into only one cell or tissue type; multipotent, a stem cell able to develop into more than one cell type of the plant body; pluripotent, a stem cell able to develop into most, but not all, cell types that constitute the body; and totipotent, a stem cell able to develop into all cell types. These are reflected by case studies that use various cell and tissue culture methodologies, such as callus culture, tracheary element formation, adventitious bud/root formation, and somatic embryogenesis [ 8 , 9 , 10 , 11 ]. However, to date, there are no definite and highly efficient standards for the regulation of stem cell development in in vitro plant cell and tissue cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In glossaries, for example [ 7 ], stem cell developmental potency is classified into several types: unipotent, a stem cell able to develop into only one cell or tissue type; multipotent, a stem cell able to develop into more than one cell type of the plant body; pluripotent, a stem cell able to develop into most, but not all, cell types that constitute the body; and totipotent, a stem cell able to develop into all cell types. These are reflected by case studies that use various cell and tissue culture methodologies, such as callus culture, tracheary element formation, adventitious bud/root formation, and somatic embryogenesis [ 8 , 9 , 10 , 11 ]. However, to date, there are no definite and highly efficient standards for the regulation of stem cell development in in vitro plant cell and tissue cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Only four CesA genes were upregulated exclusively in induced samples (at the transition from 0 to 12 h), but none of them are potential homologs to rice secondary wall CesAs ( Supplementary Table S7). Similar results were found for a xylogenic culture of the woody bamboo species Phyllostachys nigra, in which SCW-related CesAs were not upregulated upon inducing conditions (Ogita et al, 2018). Noteworthy, the determination of CesAs specificities in primary or secondary wall deposition in sugarcane has been problematic.…”
Section: Scw-related Genes Are Upregulated During the Differentiationsupporting
confidence: 68%
“…The identification of WRKYs from different groups within the family with a role in regulating the NAC-MYB network in different cell types indicates that there is still much to be explored in terms of regulation of SCW deposition. For instance, TFs from the GRAS family are interesting candidates for further analysis, as these TFs have been systematically found as co-expressed with SCW biosynthetic genes in different species, such as Arabidopsis (Rao et al, 2019), bamboo (Ogita et al, 2018), switchgrass (Rao et al, 2017(Rao et al, , 2019, and Miscanthus (Hu et al, 2017), and were also found in the sugarcane network ( Figure 7A).…”
Section: Co-expression Network Analysis Allowed the Identification Ofmentioning
confidence: 99%
“…After induction, changes in cell morphology, cell wall composition and structure, and transcript and metabolite abundances can be investigated by harvesting differentiating cells at different time points (Devillard and Walter, 2014). Xylogenic cultures have been successfully employed to unravel and characterize developmental processes associated with xylogenesis, such as xylem differentiation, SCW deposition and programmed cell death in different plant species (Kubo et al, 2005;Yamagishi et al, 2013;Devillard and Walter, 2014;Ogita et al, 2018). Here, we report on the establishment of a xylogenic culture as a model system to study SCW deposition in sugarcane.…”
Section: Introductionmentioning
confidence: 99%